Modelling unfolding response data within the structural equation modelling framework - Lim, Jie Xin (2015)
The dominance and the unfolding response mechanisms have been proposed to describe the way individuals response to items. Methods to model the unfolding response data have been proposed from various frameworks. However, these methods are less acquainted by researchers in the social sciences and some require specialised software for implementation. This thesis addressed this issue by proposing to model the unfolding response data within the general SEM framework through Mplus which is widely used by applied researchers. Two simulation studies were designed to examine the proposed model. Study 1a studied the effects of sample size, test length, item locations, and response options on the parameter recovery and model-data fit using simulated data. Study 1b investigated the ability of the model and the estimation method implemented in Mplus in recovering the correlation between factors. Two empirical datasets were also analysed to illustrate the application of the proposed method (OCRUM) and also to compare the performance of OCRUM with the Generalised Graded Unfolding Model (GGUM), one of the widely used methods for the analysis of unfolding response data. This thesis concluded with limitation of the proposed model and areas for future research were identified.